(untitled) (Archive of Conferences, 2022)
One of the brightest and most unique examples of modern storytelling, which has become a novelty in literature, is Nazar Eshankul’s story "You Can’t Catch the Wind". In this article, we take a closer look at the literary analysis of this story.